Gender, caring work, and the embodiment of kufungisisa: Findings from a global health intervention in Shurugwi District, Zimbabwe. (November 2022) - Brown, Tim; Datta, Kavita; Fernando, Shamiso
Abstract: This paper analyses the findings from qualitative interviews conducted as part of a cross-disciplinary pilot study into the efficacy of the Friendship Bench for promoting mental health amongst rural women living in Shurugwi District, Zimbabwe. Informed by UNICEF's nurturing care framework, the pilot study hypothesised that women's caring capabilities would be enhanced if a cost-effective intervention could be found for those suffering from common mental disorders (CMD), locally referred to as kufungisisa . Focusing on the women's accounts of their embodiment of kufungisisa, the paper further highlights the important role that gender plays in women's experience of common mental health disorders. More critically, it identifies the ways in which patriarchal social relations may be reinforced through the spaces of global health interventions such as the one reported on here. The paper concludes with a moment of self-reflection. Specifically, it poses the question that our paper, and the global health intervention it reports upon, would look very different if the women's experiences of kufungisisa were considered not only as they appear in the present but at the intersection of social and spatial relations that have much longer histories. Highlights: Patriarchal social relations continue to frame women's experience of mental ill health in rural Zimbabwe. Gendered social relations operate in and through the spaces of global health interventions. The slow violence of settler colonialism remains under researched in global public health interventions.